Writing Case Reports: Teaching and Tuition Techniques, and the Improvement of Clinical Diagnostic Reasoning - Yosuke Kakisaka; Yosuke Kakisaka; Mayu Fujikawa; Schuyler Gaillard (University Library System, University of Pittsburgh, 2016)
NA